Beyond Quantitative Measures: Researching Identity Formation and Development through the Qualitative Paradigm (Context: Journal of Interdisciplinary Studies, 2023)
The m ain objective of this paper is to explore the potential of the qualitative research paradigm in addressing complex topics related to identity formation and development. There has been a shift in conceptualizations of education’s purpose, with scholars arguing that the paradigm of identity formation (rather than the paradigm of preparation) should be promoted in educational contexts. This implies that education should aim to enhance personhood and facilitate the formation of personal identities in young individuals. Traditional quantitative studies, relying on statistical analyses of numerical data, are becoming less effective in providing insights into the increasingly diverse pathways of human development and the dynamic environments in which they take place. Quantification of human experience and development is encountering a growing pushback in the postmodernity. Conversely, the qualitative research paradigm offers a fresh and authentic perspective by delving into real-life biographies and encompassing the entirety of human experience. However, it is important to note that the qualitative paradigm has specific epistemological characteristics that define the scope of inquiry it generates.